KONSEP PENDIDIK DALAM ISLAM - Sudarto, Sudarto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2022)
Educators are people who play an important role in educating the nation's children, while educators who speak what comes to our minds are adults who guide and give us something we don't know. The method used in this study is using qualitative methods, the characteristic of this approach lies in its hope of describing a case by capturing its interests and side effects, with the aim that the examination of the information used is scientifically enlightening. Information collection was carried out through library research techniques. From the results of this study it is known that in Islamic education,